Insulin resistance and daytime sleepiness in patients with sleep apnoea. Issue 11 (5th June 2008) - Barceló, A; Barbé, F; de la Peña, M; Martinez, P; Soriano, J B; Piérola, J; Agustí, A G N
Abstract : Background: Excessive daytime sleepiness (EDS), obesity and insulin resistance (IR) occur frequently in patients with obstructive sleep apnoea syndrome (OSAS). We hypothesised that in these patients, EDS is a marker of IR, independent of obesity. Methods: We studied 44 patients with OSAS (22 with and 22 without EDS) matched for age (±5 years), body mass index (BMI ±3 kg/m 2 ) and severity of OSAS (as determined by the apnoea–hypopnoea index (AHI)), and 23 healthy controls. Patients (n = 35) were re-examined after 3 months of effective therapy with continuous positive airway pressure (CPAP). EDS was assessed by both subjective (Epworth Sleepiness Scale) and objective (Multiple Sleep Latency Test) methods. IR was determined by the HOMA index. Serum levels of glucose, triglycerides, cholesterol, cortisol, insulin, thyrotropin, growth hormone and insulin-like growth factor I (IGF-I) were also determined. Results: Despite the fact that age, BMI and AHI were similar, patients with EDS had higher plasma levels of glucose (p<0.05) and insulin (p<0.01), as well as evidence of IR (p<0.01) compared with patients without EDS or healthy controls. CPAP treatment reduced cholesterol, insulin and the HOMA index and increased IGF-1 levels in patients with EDS, but did not modify any of these variables in patients without EDS. Conclusion: EDS in OSAS is associated with IR, independent of obesity. Hence EDS may be a useful clinical marker to identify patients with OSAS at risk of metabolic syndrome.